INTRACARDIAC AND CENTRAL HEMODYNAMIC CHANGES IN ELDERLY PATIENTS WITH ISOLATED SYSTOLIC ARTERIAL HYPERTENSION - Z. T. Astakhova; V. A. Aydarova; R. V. Enaldieva; F. U. Kanukova (Российский кардиологический журнал, 2009)
The changes in central and intracardiac hemodynamics were investigated among elderly patients with isolated systolic and systolo-diastolic arterial hypertension (ISAH, SDAH). Inn total, 102 patients with Stage I-II AH were divided into two groups: the main group (37 ISAH individuals) and the control group (65 participants with SDAH), comparable by age and gender structure. All participants underwent standard Doppler echocardiography. Left ventricular (LV) stroke volume, LV endsystolic and end-diastolic sizes, ejection fraction (%), and ΔS (%) were registered. LV myocardial mass (LVMM) and LVMM index were calculated. Total peripheral resistance was assessed non-invasively, using standard formulae. In ISAH patients, disturbances of intracardiac and central hemodynamics and LV geometry were observed, which should be considered while assessing risk level, disease prognosis, and potential therapeutic strategies.